2008
DOI: 10.1259/bjr/22775594
|View full text |Cite
|
Sign up to set email alerts
|

Fetal radiation dose from CT pulmonary angiography in late pregnancy: a phantom study

Abstract: Pulmonary embolism (PE) is the leading direct cause of maternal mortality in the UK. Accurate diagnosis is important but, even though CT pulmonary angiography (CTPA) is the recommended imaging modality for PE in the general population, there is limited guidance for pregnant patients. Knowledge of the radiation doses to both the mother and the fetus is therefore important in the justification of CTPA in this situation. Dose measurements were made on three helical CT scanners, with an anthropomorphic phantom rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 13 publications
3
35
0
Order By: Relevance
“…Apparently, the patient radiation burden from CTPA may be considerably reduced if a modern CT scanner is used. Besides, the embryo/fetal dose from CTPA studies has been reported to be 0.06-0.23 mGy during the third trimester of pregnancy (26), which agrees with our findings of 0.05-0.28 mGy. Discordantly, Hurwittz et al (27) reported an embryo/fetal dose of 0.24-0.66 mGy from CTPA studies performed on pregnant patients with suspected PE during the first trimester.…”
Section: Discussionsupporting
confidence: 92%
“…Apparently, the patient radiation burden from CTPA may be considerably reduced if a modern CT scanner is used. Besides, the embryo/fetal dose from CTPA studies has been reported to be 0.06-0.23 mGy during the third trimester of pregnancy (26), which agrees with our findings of 0.05-0.28 mGy. Discordantly, Hurwittz et al (27) reported an embryo/fetal dose of 0.24-0.66 mGy from CTPA studies performed on pregnant patients with suspected PE during the first trimester.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years a number of papers have shown that abdominal shielding yields foetal dose reductions of approximately 35% in both early and late stage pregnancy when patients undergo chest CT [13][14][15]. Despite this evidence, out-of-plane shielding has not been used regularly in CT scanning even though the use of such shielding has no effect on the quality of the images produced.…”
mentioning
confidence: 99%
“…Estimated foetal radiation exposure for CTPA varies from 3.3 mGy to 130.0 mGy. However, the foetal radiation dose for V/Q scanning is estimated around 100-370 mGy, which is three times higher than CTPA [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%